“A good mother can't—But a good father should?” Cross‐ and within‐country differences in attitudes toward parents' full‐time work in 26 European countries - Salin, Milla; Tammelin, Mia; Otonkorpi‐Lehtoranta, Katri; Isoniemi, Henna (Wiley, 2026)
Regardless of the rise of egalitarian parenting, maternal and paternal roles are subject to different expectations, shaped by cultural and institutional factors. We examine levels of (dis)approval of parents' full-time work in 26 European countries and ask: Do attitudes toward mothers' and fathers' full-time work vary across countries? What are the sociodemographic, cultural, and family policy-related institutional factors that explain these attitudes? To what extent can the gender arrangement framework help to understand differences in attitudes toward full-time working parents? Data from the 2018 European Social Survey was analyzed using cross-tabulation and multilevel analysis. Results reveal that the ideal of motherhood continues to be culturally more contested than that of fatherhood. Individual-level sociodemographic factors are more relevant to attitudes toward mothers' than to fathers' full-time work, while country-level factors connected to gender, work culture, and family policy are similar in their effects on attitudes toward mothers' and fathers' full-time work.